2023
DOI: 10.3390/antiox12020247
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 and COVID-19 Outcomes: An Umbrella Review of Systematic Reviews and Meta-Analyses

Abstract: Background: The immune system (innate and adaptive) is influenced by vitamin D3, which affects gene expression and inflammatory pathways. An umbrella review was conducted to evaluate the power and accuracy of data connecting vitamin D3 to the outcomes of COVID-19 infection and to appraise the proof provided by published meta-analyses. Methods: MEDLINE, Embase, and the Cochrane Library were searched from database inception to 31 May 2022. Meta-analyses of prospective or retrospective observational studies and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…5), indicating higher induction of VDR signaling in DCs and macrophages potentially inducing antimicrobial or antiviral proteins like β-defensins and cathelicidins. While defensins protects the host cells by disrupting microbial membranes including SARS-CoV-2, cathelicidins attract various immune cells via chemotaxis and also enhance phagocytosis by macrophages, increasing vascular permeability and ultimately activation of B and proliferation of T cells (12), thus strengthening innate immune responses that appear to be augmented by calcifediol supplementation.…”
Section: Upregulation Of Innate and Adaptive Immune Signaling Pathway...mentioning
confidence: 99%
See 2 more Smart Citations
“…5), indicating higher induction of VDR signaling in DCs and macrophages potentially inducing antimicrobial or antiviral proteins like β-defensins and cathelicidins. While defensins protects the host cells by disrupting microbial membranes including SARS-CoV-2, cathelicidins attract various immune cells via chemotaxis and also enhance phagocytosis by macrophages, increasing vascular permeability and ultimately activation of B and proliferation of T cells (12), thus strengthening innate immune responses that appear to be augmented by calcifediol supplementation.…”
Section: Upregulation Of Innate and Adaptive Immune Signaling Pathway...mentioning
confidence: 99%
“…Low levels of vitamin D have been linked to diseases like in ammatory bowel disease (7) and a higher risk of respiratory infections, such as COVID-19, in uenza as well as autoimmune diseases (8,9). Various studies and meta-analysis during COVID-19 pandemic indeed found an association between low vitamin D levels and a higher risk of severe COVID-19 outcomes, such as hospitalization and death (10)(11)(12)(13). The proposition has been put forward that activation of VDR may have the capacity to decrease the likelihood of acute respiratory distress syndrome (ARDS), cardiac complications, coagulopathy, and mortality in patients with COVID-19 (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 29 observational studies were published from January 2022 to August 2023, confirming the previous conclusion. In a very large population-based meta-analyses study by Petrelli et al ( 2023 ), including 74 articles, 27 meta-analyses noted that vitamin D3 deficiency or insufficiency is associated with increased risk of SARS-CoV-2 infection, COVID-19 severity, and mortality risk, with highly suggestive evidence. Equally important, the results of a large number of observational groups, a retrospective case–control study published by Israel et al in 2022, showed that there is an inverse relationship between the level of VD and the risk of SARS-CoV-2 infection and disease severity in infected patients.…”
Section: Clinical Studies Of Vitamin D In Covid-19mentioning
confidence: 99%
“….25(OH)D levels was measured No intervention, No − 25(OH)D levels were inversely correlated with TNFa, TNFa mRNA, IL-6, and D-dimer levels—The lower mortality and severity of COVID-19 patients was with higher 25(OH)D levels Beheshti et al 2023 Observational cohort study 288 patients 2 boluses of calcifediol of 450 µg each for 2 consecutive days for a total of 900 mcg The percentage of deaths was significantly higher in patients who did not receive calcifediol Longer duration of hospitalization in patients with severe 25OHD deficiency This study demonstrated that best prognosis of COVID-19 patients with adequate vitamin D levels and patients treated with calcifediol supplementation Mingiano et al 2023 Meta-analyses 74 Studies, 27 meta-analyses, 12,767,045 patients Various Various Low levels of vitamin D3 were associated with significant risk of severity,mortality compared to patients with sufficient levels. Vitamin D3 supplementation, was associated with significantly reduced infection, mortality, infection severity Petrelli et al 2023 Prospective cohort study observational study 191 patients No intervention No intervention Lower serum 25(OH)D levels were significantly associated with an increased number of,the severity of COVID, mechanical vent. However, patients with either sufficient or insufficient vitamin D levels did not develop mortality Rachman et al 2023 A case–control study Observational study 46 patients No intervention No This study showing an association between low serum vitamin D and ARTIs including COVID-19 Elmi et al 2023 Retrospective observational study, Poland, 134 healthy subjects, assessing the Incidence of infection after one year No intervention No Increased risk of COVID-19 infection was only observed in those with severe 25OHD deficiency < 12 ng/mL Basińska-Lewandowska et al ...…”
Section: Clinical Studies Of Vitamin D In Covid-19mentioning
confidence: 99%